Aplicação de princípios de qualidade de dados durante o desenvolvimento de um sistema computacional médico para a cirurgia coloproctológica - Jung, Wilson (2012)
Lately, many human knowledge ﬁelds use computer systems to support data management which are the foundation to the decision making process. Data Quality (DQ) is a key feature whose absence can undermine the usefulness of the information and the processes that use it. There can be found in the literature several cases of DQ problems with impact in many areas, resulting in economic and social losses. Therefore, DQ research aims to study data problems causes and proposes assessment methods and processes to assist in quality assurance. In healthcare, data constitutes an important element used as the basis for applying medical treatments and procedures to patients, thus requiring a high quality level. The data is also used in the research and application of computational knowledge discovery methods, such as Data Mining. Therefore, the goal of this work is to study the implementation of principles to assist DQ guarantee during the medical software development. This goal motivated the development of a case study related to Coloproctology, in which a surgery data management system prototype was de- veloped in partnership with the Coloproctology Service of FCM - UNICAMP. The interaction with domain experts was a key factor during the development process, providing the adequate data structure modeling that composes the system. A module to monitor speciﬁc data problems has also been incorporated into the prototype to assist the appropriate information insertion as much as the control of patients records which have DQ problems. The prototype has been evaluated by computer and healthcare s colaborators, who, after using the system, answered to a qualitative DQ assessment form. The assessment s results pointed out the prototype suitability to the activities it is aimed for, guided speciﬁc functionalities review and may support the proposed software evolution and future related work.